2012
DOI: 10.1016/j.marpolbul.2012.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Metazooplankton communities in the Ahe atoll lagoon (Tuamotu Archipelago, French Polynesia): Spatiotemporal variations and trophic relationships

Abstract: Metazooplankton abundance, biomass (<80 μm, 200-500 μm and >500 μm) and community structure in the Ahe atoll were studied together with their relationships with environmental factors (temperature, salinity, wind) and trophic factors (phytoplankton, bacteria, heterotrophic nanoflagellates (HNF) and ciliates) during three periods in 2008-2009. Meroplankton, mainly bivalve and gastropod larvae, was dominant. Holoplankton was dominated by copepods, the main species being Oithona spp., Paracalanus parvus, Clausocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Previous studies in French Polynesian atolls have shown that plankton concentration variations can be significant at small spatial and/or temporal scale, despite the average low concentrations and the weak seasonal differences (Buestel and Pouvreau, 2000;Charpy et al, 2012;Fournier et al, 2012, González et al, 1998Pagano et al, 2012;Sournia and Ricard, 1976;Thomas et al, 2010). However, the exact mechanisms responsible for these changes remain unclear.…”
Section: Hydrobiological Parametersmentioning
confidence: 99%
“…Previous studies in French Polynesian atolls have shown that plankton concentration variations can be significant at small spatial and/or temporal scale, despite the average low concentrations and the weak seasonal differences (Buestel and Pouvreau, 2000;Charpy et al, 2012;Fournier et al, 2012, González et al, 1998Pagano et al, 2012;Sournia and Ricard, 1976;Thomas et al, 2010). However, the exact mechanisms responsible for these changes remain unclear.…”
Section: Hydrobiological Parametersmentioning
confidence: 99%
“…These observations are unusual in Tuamotu atoll lagoons where the biomass of >2 lm planktonic particles is approximately 36% of the total planktonic biomass, as reviewed by Pouvreau et al (2000a). Previous studies in French Polynesian atolls have shown that plankton concentration variations can be significant at small spatial and/or temporal scale, despite the average low concentration of plankton and despite weak seasonal trends (Buestel and Pouvreau, 2000;Charpy et al, 2012;Fournier et al, 2012;González et al, 1998;Pagano et al, 2012;Sournia and Ricard, 1976;Thomas et al, 2010). However, the exact mechanisms responsible for these changes remain unclear.…”
Section: Tablementioning
confidence: 78%
“…Despite their average low abundance, transitory peaks of diatoms, bivalve larvae and other metazoan larvae concentration have been observed in atoll lagoons Pagano et al, 2012;Sournia and Ricard, 1976). These plankton fractions may therefore represent significant food sources for pearl oysters.…”
Section: Discussionmentioning
confidence: 99%
“…This leads subsequently to an increase in bacterial production and a stimulation of the microbial loop and impacts the higher trophic levels of the food web (Ferrier- Pages and Gattuso, 1998). In Ahe atoll, the microbial loop has been described as predominant (Pagano et al, 2012) and the community as heterotrophic. This finding is supported by spatio-temporal pervasiveness found in this study for heterotrophic groups such as Marinovum, Flavobacteria and Erytrobacter.…”
Section: Resultsmentioning
confidence: 99%